The Effect of Workplace Stretching Exercise on Reducing Musculoskeletal Complaints in Ndao Ikat Weaving Workers in Rote Ndao District - Serlien A. Luik; Jacob M. Ratu; Agus Setyobudi (Lontar : Journal of Community Health, 2021)
Musculoskeletal complaints in Ndao weaving workers are a problem of muscle disorders for weavers. As a result of this process is a long time and repeatedly will cause musculoskeletal complaints. Workplace Stretching Exercise is designed with the principle of muscle stretching, which is an attempt to extend muscle rest or relaxation. This activity will improve blood circulation so that it helps relax nervous tension and train muscles to be stronger so they don't get tired easily while working. This study aimed to analyze the effect of workplace stretching exercises on the reduction of musculoskeletal complaints in Ndao weaving workers in Rote Ndao Regency. This is a quantitative research with a pre-experimental design type one-group pretest-posttest design method. The population in this study were active weavers in Ikat Ndao weaving, Lobalain District as many as 40 weavers. The selected research sample has met the eligibility criteria for as many as 18 active weavers. The type of analysis test used is the paired sample t-test. The results showed that there was a difference in the level of musculoskeletal complaints before the intervention was in the moderate complaint category with a percentage of 77.8% and after the WSE intervention, the complaints decreased to the low complaint category with a percentage of 66.7% with a significant decrease in value of 19.39%. The results of the analysis show that there is an effect of Workplace Stretching Exercise on the reduction of musculoskeletal complaints in Ndao tie weaving workers, where there is a large difference in value (p = 0.007 ) ≤ (0.05), so it is expected that Ndao tie weaving workers will carry out Workplace Stretching Exercise activities every day in between weaving activities to reduce musculoskeletal complaints.